Avaliação das atividades antioxidante e anti-inflamatória do sesamol em modelos experimentais in vitro - Duarte, Adriane Ribeiro (2018)
Inflammation is associated with redox and mitochondrial dysfunctions, which also leads to bioenergetics decline. Therefore, it is necessary to find anti-inflammatory agents that exert mitochondrial protection during inflammation. In this context, sesamol has been viewed as an antioxidant and anti-inflammatory bioactive molecule, as examined in both in vitro and in vivo experimental models. However, it was not previously evaluated whether sesamol would protect mitochondria of mammalian cells undergoing inflammation. With this in mind, we analyzed, in the herein presented work, whether a pretreatment (1 h) with sesamol (at 1, 10, 50 e 100 µM) would promote mitochondrial protection in RAW 264.7 cells exposed to lipopolysaccharide (LPS) in an in vitro experimental model of inflammation. Besides, we examined whether the cytoprotective enzyme heme oxygenase-1 (HO-1) would mediate the sesamol-induced mitochondrial protection in RAW 264.7 cells. Sesamol pretreatment decreased the LPS-induced redox impairment in the membranes of mitochondria. Moreover, sesamol reduced the production of reactive species, such as superoxide anion radical (O2 -• ) and nitric oxide (NO• ), in LPS-treated RAW 264.7 cells. We also evidenced that sesamol decreased the impact of LPS on the activity of the mitochondrial complexes I and V and on the production of adenosine triphosphate (ATP). Sesamol was also efficient in preventing the loss of mitochondrial membrane potential (MMP) caused by LPS in the RAW 264.7 cells. In this context, sesamol blocked the LPS-induced mitochondriadependent cell death by apoptosis. Sesamol also exerted anti-inflammatory effects by reducing the secretion of pro-inflammatory cytokines, such as interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α), among others, in this experimental model. The mitochondrial protection and the anti-inflammatory effects caused by sesamol were dependent on the HO-1 enzyme, since its inhibition by ZnPP IX (at 20 µM) blocked the cytoprotection observed here. Thus, sesamol caused mitochondrial protection and antiinflammatory effects by a HO-1-dependent manner.